Reshaping the university: New relationships between research, scholarship and teaching - Barnett, Ronald (Open University Press / Society for Research into Higher Education, 2005)
What is the emerging shape of the University? Are there spaces for present activities to be practised anew or even for new activities? If these questions have force, they show that the metaphors of shapes and spaces can be helpful in understanding the contemporary university.Research, teaching and scholarship remain the dominant activities in universities and so it is their relationships that form the main concerns of this volume. Are these activities pulling apart from each other? Or might these activities be brought more together in illuminating ways? Is there space to redesign these activities so that they shed light on each other? Is there room for yet other purposes? In this volume, a distinguished set of scholars engage with these pertinent but challenging issues. Ideas are offered, and evidence is marshalled, of practices that suggest a re-shaping of the University may be possible. Reshaping the University appeals to those who are interested in the future of universities, including students, researchers, managers and policy makers. It also addresses global issues and it will, therefore, interest the higher education community worldwide.
OCLC: ocm58828001